Frequency and Severity of Periodontitis in the Patients with Psoriasis - Maryam Jalili Sadrabad; Ramin Taheri; Mahla Sadat Saremi; Sina Ebrahimi; Shabnam Sohanian (Journal of Mazandaran University of Medical Sciences, 2021)
Background and purpose: Psoriasis is a chronic inflammatory genodermatosis, and periodontitis is an inflammatory disease of the protective tissue of the tooth. There is increasing prevalence of psoriasis and periodontitis and some studies indicated a relationship between psoriasis and periodontitis. The purpose of this investigation was to study the frequency and severity of periodontitis in patients with psoriasis. Materials and methods: In this study, the severity of psoriasis and mouth and teeth examination results of 40 patients were recorded. Tooth looseness, number of missing teeth, bleeding on probing, and clinical attachment loss were measured using periodontal probe. Data analysis was carried out applying t test, Chi square, and correlation coefficient. Results: The overall prevalence of periodontal diseases was 80%, including loose teeth (10%), missing teeth (47.5%), gingival bleeding (60%), and gingival resorption (62.5%). Periodontal diseases were found to be significantly associated with duration and severity of psoriasis (P = 0.032 and P <0.001, respectively). Also, there was a significant association between severity of periodontal diseases and duration and severity of psoriasis (P = 0.048 and P = 0.023, respectively). Conclusion: According to this study, periodontal diseases are highly prevalent in patients with psoriasis which are associated with severity and duration of psoriasis. Inflammatory process is involved in both diseases, so, accurate oral examinations for periodontal diseases are strongly suggested in patients with psoriasis.